Proceedings of the 1st International Conference on Innovation in Education (ICoIE 2018) 2019
DOI: 10.2991/icoie-18.2019.106
|View full text |Cite
|
Sign up to set email alerts
|

Student Perspective in Using Social Media As a Tool in English Language Learning

Abstract: Social media has great potential to support student-centered learning as they are flexible, interactive, and resource-rich in nature. One of its drawbacks is the quality of online instruction that lead to unfavorable perception and perspective of the students. The objectives of this research are to analyze the students' perceptions and perspectives in using Social Media as a tool in English Language learning. Qualitative and quantitative data were collected from the students of the English Department, Faculty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
(4 reference statements)
2
9
0
Order By: Relevance
“…The present study also revealed that the participants developed new vocabulary by reading English posts, and captions, listening to English videos, and chatting in English. It is in line with a study conducted by Ismail et al (2018) that there were 67 % of student respondents stated that social media has improved their vocabulary through many ways. In this respect, Benidir (2017) explains that Social media can help in learning and teaching vocabulary and can be incorporated into learners' life which can facilitate learners to develop their vocabulary knowledge.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present study also revealed that the participants developed new vocabulary by reading English posts, and captions, listening to English videos, and chatting in English. It is in line with a study conducted by Ismail et al (2018) that there were 67 % of student respondents stated that social media has improved their vocabulary through many ways. In this respect, Benidir (2017) explains that Social media can help in learning and teaching vocabulary and can be incorporated into learners' life which can facilitate learners to develop their vocabulary knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Nasrullah and Khan (2019) in their study reported that students beleived by using social media, they noticed some improvement on their communication skills and they could have conversation with other people at any time. In addition students are in favor of using social media as it helps them learn to improve their English skills due the fact that it is accessible and handy (Ismail et al, 2018).…”
Section: Social Media Use For Learning Englishmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas, according to Ismail(2019), he found that there were 74% of the respondents agree that the inculcation of social media within the classroom context established positive consequences on the learning activity. Consequently, by referring to Alnatsheh, (2018), the researchers have concluded that SNSs, have huge positive consequences for the educational process, and that flexibility can be achieved.…”
Section: Perception On the Use Of Snssmentioning
confidence: 95%
“…Social media can be in the form of audio sharing applications, blogging applications, micro-blogging applications, social networking services, voice over the internet, academic networking sites, and others (Chisenga, Kedemi, & Sam, 2014). With the saturation of social media into students' daily life, many experts and researchers have explored the use of social media for teaching and learning, including language learning (Anggraeni, 2018;Boholano, 2017;Hamadeh, Bahous, Diab, & Nabhani, 2020;Lau, 2018;Mondahl & Razmerita, 2014;Wu & Marek, 2018) and English language learning (Alwehaibi, 2015;Espinosa, 2015;Ismail, Ahmad, Zaim, Mukhaiyar, & Gistituati, 2019;Listiani, Suwastini, Dantes, Adnyani, & Jayantini, 2021).…”
Section: Introductionmentioning
confidence: 99%